(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study was conducted to investigate COVID-19 prevention practices among residents in Nha Trang city, Khanh Hoa province, in 2022. Methods: A cross-sectional study was implemented, collecting data from 538 residents through face-to-face interviews on COVID-19 prevention practices. Results: 79.2% of participants demonstrated adequate overall COVID-19 prevention practices. Specifically, the compliance rates for adaptive prevention measures and consistent preventive behaviors were 66% and 83.5%, respectively. Factors significantly associated with proper COVID-19 prevention practices included ethnicity, household living arrangements, number of COVID-19 vaccine doses received, and attitudes toward pandemic prevention. Conclusion: To enhance COVID-19 prevention efficacy in Nha Trang, local health authorities should target communication campaigns toward ethnic minorities and multi-generational households, promote full and booster vaccination coverage, implement behavioral change programs to foster positive attitudes, and establish periodic epidemic surveillance process.